গণতন্ত্র - মুহাম্মদ জাহাঙ্গীর. (ঢাকা : মাওলা ব্রাদার্স, 2006)
Contributed articles on democracy with reference to the political conditions of Bangladesh.
গ্রন্থপুঞ্জিগত নির্দেশিকা
In Bengali.
Keywords: Democracy -- Bangladesh; Bangladesh -- Politics and government -- 1971-